Application of TGA/c-DTA for Distinguishing between Two Forms of Naproxen in Pharmaceutical Preparations - Paweł Ramos; Barbara Klaudia Raczak; Daniele Silvestri; Stanisław Wacławek (Pharmaceutics, 2023)
Naproxen is one of the most used non-steroidal anti-inflammatory drugs (NSAIDs). It is used to treat pain of various origins, inflammation and fever. Pharmaceutical preparations containing naproxen are available with prescription and over-the-counter (OTC). Naproxen in pharmaceutical preparations is used in the form of acid and sodium salt. From the point of view of pharmaceutical analysis, it is crucial to distinguish between these two forms of drugs. There are many costly and laborious methods to do this. Therefore, new, faster, cheaper and, at the same time, simple-to-perform identification methods are sought. In the conducted studies, thermal methods such as thermogravimetry (TGA) supported by calculated differential thermal analysis (c-DTA) were proposed to identify the type of naproxen in commercially available pharmaceutical preparations. In addition, the thermal methods used were compared with pharmacopoeial methods for the identification of compounds, such as high-performance liquid chromatography (HPLC), Fourier-transform infrared spectroscopy (FTIR), UV-Vis spectrophotometry, and a simple colorimetric analyses. In addition, using nabumetone, a close structural analog of naproxen, the specificity of the TGA and c-DTA methods was assessed. Studies have shown that the thermal analyses used are effective and selective in distinguishing the form of naproxen in pharmaceutical preparations. This indicates the potential possibility of using TGA supported by c-DTA as an alternative method.